2015
DOI: 10.14720/aas.2014.103.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of spinach (Spinacia oleracea L.) landraces collected in Iran using some morphological traits

Abstract: Spinach has become an important vegetable crop in most regions of the world and remarkable changes in production amounts have occurred in the past decades due to demand increase in many countries. Fifty-four spinach landraces collected from diverse geographical regions of Iran were evaluated for several qualitative and quantitative traits. Landraces indicated a high variability for measured morphologic characteristics regarding results of variance analysis and descriptive statistics. The first three factors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 8 publications
1
22
0
1
Order By: Relevance
“…PCA of present results has indicated that seed, leaf and anthocyanin-related traits are the main variability contributing factors. Similar to this, Sabaghnia et al [1] also reported leaf trait as the most important factor contributing towards variability of spinach germplasm. Figures S1 and S2 represented biplot analyses showing variability among accessions based on their geographical locations and different morphological traits.…”
Section: Principle Component Analysissupporting
confidence: 71%
See 2 more Smart Citations
“…PCA of present results has indicated that seed, leaf and anthocyanin-related traits are the main variability contributing factors. Similar to this, Sabaghnia et al [1] also reported leaf trait as the most important factor contributing towards variability of spinach germplasm. Figures S1 and S2 represented biplot analyses showing variability among accessions based on their geographical locations and different morphological traits.…”
Section: Principle Component Analysissupporting
confidence: 71%
“…Accumulation of variables in a closed region indicates the positive correlation among them [25]. A similar plot was built by Arif et al [19] and Sabaghnia et al [1] to show the correlation of different morphological features. In the present results, the two main factors collectively represented 38-41% variability during both years of growth.…”
Section: Principle Component Analysismentioning
confidence: 84%
See 1 more Smart Citation
“…Multiple emergences of the smooth phenotype may have independently occurred as the presence or absence of prickles is controlled by a single gene, with spines being dominant over smoothness (Pandey and Kalloo 1993). The smooth phenotype has also been observed in landraces from the Middle East (Sabaghnia et al 2014;Mohebodini et al 2017).…”
Section: Domestication Syndromementioning
confidence: 74%
“…The results suggested that Northern and Southern Chinese spinach populations may have different origins. Sabaghnia et al (2014) [ 14 ] examined 54 spinach landraces collected from diverse geographical regions of Iran and divided the landraces into sixteen clusters based on for several qualitative and quantitative trait data. Ebadi-Segheloo et al (2014) [ 15 ] evaluated 121 spinach landraces, collected from the various spinach growing areas of Iran, using several agro-morphological traits such as leaf area, leaf width, petiole length, petiole diameter, seed yield and 1000-seed weight and identified six clusters with each cluster having some specific unique characteristics.…”
Section: Introductionmentioning
confidence: 99%